Fresno Merced Counties Legal Services Baby Shower For Leroy and Joanna Cordova - Watkins, Howard::::::::: (1982)
Women's International League for Peace and Freedom banned bus poster: "Why is this the only job our government has to offer 18 year olds? THINK BEFORE YOU REGISTER FOR THE DRAFT"